2009
DOI: 10.1001/archdermatol.2009.229
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat for the Treatment of Bullous Pemphigoid in the Setting of Advanced, Refractory Cutaneous T-Cell Lymphoma

Abstract: Histone deacetylase (HDAC) inhibitors represent a novel class of medication that is being targeted for use in the treatment of cancer. A member of this class, vorinostat, has recently been approved for the therapy of cutaneous T-cell lymphoma. Importantly, emerging data from animal studies have indicated that HDAC inhibitors may have the capacity to potently suppress the development of autoimmune disease. In this report, we describe a patient with advanced cutaneous T-cell lymphoma who developed refractory bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Furthermore, HDACis have been shown to downregulate proinflammatory cytokines in mouse models of autoimmune diseases such as, arthritis, asthma, colitis, graft versus host disease, and systemic lupus erythematosus [29, 30, 49–53]. Similar effects have been observed in humans and we previously reported the resolution of the autoimmune blistering disease bullous pemphigoid in a CTCL patient treated with an HDACi [28]. There are also case reports associating the reactivation of latent herpes viruses with HDACi treatment suggesting that HDACis suppress antiviral immunity [25, 26].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, HDACis have been shown to downregulate proinflammatory cytokines in mouse models of autoimmune diseases such as, arthritis, asthma, colitis, graft versus host disease, and systemic lupus erythematosus [29, 30, 49–53]. Similar effects have been observed in humans and we previously reported the resolution of the autoimmune blistering disease bullous pemphigoid in a CTCL patient treated with an HDACi [28]. There are also case reports associating the reactivation of latent herpes viruses with HDACi treatment suggesting that HDACis suppress antiviral immunity [25, 26].…”
Section: Discussionsupporting
confidence: 54%
“…In vitro experiments have also shown that HDACis enhance human regulatory T‐cell (Treg) suppressive function and increase the proportion of CTLA4 hi Tregs in suppression assays [27]. Consistent with these findings, HDACis have shown therapeutic benefit in animal models of autoimmune diseases and we previously reported the rapid resolution of an autoimmune blistering disorder in a CTCL patient treated with the HDACi vorinostat [28–32].…”
Section: Introductionsupporting
confidence: 58%
“…studied the incidence of internal malignancy in 1113 cases of BP in Japan, they did not observe an association between BP and MF. Thus far, only three reports describe the association of MF with BP and report the treatment of blistering skin lesions of BP that developed after MF with a regimen including ultraviolet phototherapy . To our knowledge, this is the first case of MF bullosa with the occurrence of BP.…”
mentioning
confidence: 89%
“…Vorinostat has been effective in treating the autoimmune blistering disease bullous pemphigoid. 22 There is also anecdotal support for the use of nicotinamide, either topical or oral, as an adjunctive therapy for pemphigus. [23][24][25] Future studies may further delineate the specific protein targets of the different histone deacetylase inhibitors, leading to more effective and potentially safer therapies for these life-threatening skin diseases.…”
Section: From Bench To Bedsidementioning
confidence: 99%